Impact of nanoparticle shapes on the heat transfer properties of Cu and CuO nanofluids flowing over a stretching surface with slip effects: A computational study - Algehyne Ebrahem A.; Yasmin Humaira; Alamrani Fahad Maqbul; Alduais Fuad S.; Al-Bossly Afrah (Open Physics)
This study investigates thermally radiative nanofluid flows on an elongating surface using porous media. The flow dynamics are affected by the combined impacts of exponential and thermally dependent heat sources. Additionally, magnetic effects are introduced to the flow system while it is inclined. Copper (Cu) and copper oxide (CuO) nanoparticles are mixed in water (H2O) to fabricate nanofluid flows. Different shapes of Cu and CuO nanoparticles, including column, sphere, hexahedron, tetrahedron, and lamina, were studied in this analysis. The system flow is triggered by the stretching properties of the sheet. The textured surface of the stretching sheet facilitates the exploration of the slip velocity phenomenon. The modeled equations are evaluated using the bvp4c approach in a dimensionless form. The present study is validated by comparing its findings with established datasets available in the literature. The results of this analysis show that the velocity distributions decline with increasing values of the porosity factor, velocity slip factor, and magnetic factor. The reduction in velocity profiles is quite significant in the case of Cu–water nanofluid, in contrast to the CuO–water nanofluid due to more dominance of resistive constraints in the case of the Cu–water nanofluid. The thermal distribution increases with an increase in the magnetic factor, radiation factor, Eckert number, thermal-dependent heat source, and space-based heat source, and declines with an increase in the inclination angle and thermal slip factor. The Nusselt number augments for both types of nanofluids with an increase in various emerging factors in the scenarios of thermal slip and no-slip, where an increase in the Nusselt number is maximum for the scenario where there is no thermal slip. A higher thermal distribution and heat transfer rate are determined for the lamina-shaped Cu–water and CuO–water nanofluid flows for both slip and no-slip thermal conditions. On the basis of the current findings, this study aims to design efficient cooling systems for microelectronics, improve solar thermal collectors, enhance drug delivery via heat-sensitive nanoparticles, optimize industrial heat exchangers, and advance smart textile technologies requiring controlled thermal regulation using shape-engineered Cu and CuO nanofluids.